2009
DOI: 10.1007/s11250-009-9483-8
|View full text |Cite
|
Sign up to set email alerts
|

Meat production traits of a new sheep breed called Bafra in Turkey 1. Fattening, slaughter, and carcass characteristics of lambs

Abstract: Fattening performance, slaughter, and carcass traits of Bafra ram lambs slaughtered at different weights were evaluated. A total of 40 lambs were fattened and 24 of them were slaughtered at four slaughter weights of 30, 35, 40, and 45 kg. The lambs showed decreasing fattening performance with increasing live weight. Dressing percentages and carcass compactness indices, as well as fat depots and back fat depth, were increased with greater slaughter weights. The proportions of individual cuts varied with slaught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
23
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 11 publications
15
23
5
Order By: Relevance
“…These characteristics of Karayaka male lambs in the present study were within the normal range (Olfaz et al 2005;Sen et al 2011;Sirin et al 2011) and were also found to be comparable to the native sheep breeds such as Bafra (Yakan & Unal 2010), Awassi, Morkaraman (Esenbuga et al 2009) and Kivircik (Gökdal et al 2012) of Turkey. Although the BtW and FS have an impact upon slaughter weight, carcass weight and meat quality (Sañudo et al 1998), the situation in the present study may be explained by the fact that the BW at the start of the fattening and the feed ingredients of the TMR and FCF were similar and the number of replicates per treatment was comparatively low.…”
Section: Resultssupporting
confidence: 87%
“…These characteristics of Karayaka male lambs in the present study were within the normal range (Olfaz et al 2005;Sen et al 2011;Sirin et al 2011) and were also found to be comparable to the native sheep breeds such as Bafra (Yakan & Unal 2010), Awassi, Morkaraman (Esenbuga et al 2009) and Kivircik (Gökdal et al 2012) of Turkey. Although the BtW and FS have an impact upon slaughter weight, carcass weight and meat quality (Sañudo et al 1998), the situation in the present study may be explained by the fact that the BW at the start of the fattening and the feed ingredients of the TMR and FCF were similar and the number of replicates per treatment was comparatively low.…”
Section: Resultssupporting
confidence: 87%
“…Awawdeh et al (2009), assessing lambs fed with fat sources, found greater weight gain when the source of lipid was added to the diet. Yakan & Unal (2010) found a reduction in average daily gain for lambs slaughtered at higher weights. The use of protected fat in the diet did not influence the total weight gain of lambs.…”
Section: Resultsmentioning
confidence: 91%
“…In this case, the carcasses of the heavier animals would have greater protection. Yakan & Unal (2010) found that subcutaneous fat thickness increased with increasing slaughter weight.…”
Section: Resultsmentioning
confidence: 96%
“…(2) Dressing percentage based on empty body weight. and carcass traits were calculated based on empty body weight to increase the precision of data on slaughter carcass traits (5,20,21). In the present study, the final and empty body weights were 42.560 kg and 36.400 kg, respectively.…”
Section: Slaughter Traitsmentioning
confidence: 75%
“…In order to increase yields in sheep production, genotype and environmental conditions should be improved. Hence, it has been reported that in the intensive finishing conditions of 2-3 months in Turkey, a carcass weighing 18-20 kg can be produced from a postweaned lamb of 2-3 months old (3)(4)(5)(6)(7). Based on these data, we can conclude that intensive production systems are necessary to satisfy increasing consumer demand for meat.…”
Section: Introductionmentioning
confidence: 95%